(untitled) (Rivista italiana di Paleontologia e Stratigrafia, 2002)
A high resolution cyclostratigraphic study was carried out on a cyclicaly bedded succession of late Middle Miocene deep marine deposits from the Tremiti Islands, Adriatic sea (Italy). Astronomical calibration of the sedimentary cycles provides absolute ages for different calcareous plankton bioevents, widely used for intra Mediterranean correlation, in the interval between 11.12 and 12.60 Ma. The sedimentary record of the S. nicola composite section consists of an alternation of indurated, withish coloured, CaCo3 rich and grey less indurated, CaCo3 poor marly beds, at times replaced by red coloured CaCo3 poor marls. Results of direct correlation between the La 90 (1,1) solution of the insolation curve and the cyclic lithologic patterns occurring in the studied sections, combined with results of spectral methodologies applied on the climate sensitive data (CaCo3 and Globigerinoides) showed that the classic Milankovitch periodicity can be represented through the modulation forcing of the studied sedimentary records.